2021
DOI: 10.1007/s10701-021-00463-8
|View full text |Cite
|
Sign up to set email alerts
|

Panorama Behaviors of Holographic Dark Energy Models in Modified Gravity

Abstract: Classes of solutions of field equations in) , ( T R f gravity for a Bianchi sort I (Kasner form) spacetime with matter and Holographic Dark Energy (HDE) is mentioned. Precise solutions of field equations are obtained with volumetrical power and exponential expansion laws .The physical and geometrical parameters of the models are mentioned well. The statefinder diagnostic pair and jerk parameter are analyzed to characterize utterly totally different phases of the universe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Here, this work employs the time-varying deceleration parameter suggested by Dewri (1) which shows a sign-flipping property from early-time deceleration to late-time acceleration. The model starts to expand from an initial Big Bang singularity at t = 0.25 with zero volume to de-sitter expansion at t → ∞ in which q = −1 and dH dt = 0, which matches the result of Shaikh and Wankhade's (22) . The evolution of energy density shows a positively decreasing function of time, and the pressure is always negative, which approaches zero at late times.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Here, this work employs the time-varying deceleration parameter suggested by Dewri (1) which shows a sign-flipping property from early-time deceleration to late-time acceleration. The model starts to expand from an initial Big Bang singularity at t = 0.25 with zero volume to de-sitter expansion at t → ∞ in which q = −1 and dH dt = 0, which matches the result of Shaikh and Wankhade's (22) . The evolution of energy density shows a positively decreasing function of time, and the pressure is always negative, which approaches zero at late times.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, the deceleration parameter in this study has a sign-flipping property depending on time ′ t ′ , as represented in Figure 3 (a). In Shaikh and Wankhade's (22) study of f (R, T ) gravity, the same sign-flipping deceleration parameter independent of time 't' was also noted for LRS Bianchi type-I. Also, from Equation (27), it is observed that the present value of the deceleration parameter at t 0 = 13.8 Gigayear (Gyr), is q 0 (t) = −0.730 and at t → ∞, it tends to de-sitter expansion https://www.indjst.org/ (q = −1).…”
Section: Resultsmentioning
confidence: 99%
“…Sarma [28] studied THDE in f (R, T) theory using the axially symmetric Bianchi-I space time in a recent paper. By studying volumetric power and exponential laws, Shaikh and Wankhade [29] discovered solutions in f (R, T) theory with Bianchi I Kasner form spacetime. In a different study, Varshney et al [30] looked at the equivalence of the scalar fields of tachyon, phantom, and Dirac Born-Infeld-essence with THDE in the context of f (R, T) gravity.…”
Section: Introductionmentioning
confidence: 99%